An Analysis of English language reading skills of Students: A Case Study of Faculty of Biological Sciences of University of Malakand, Khyber Pukhtunkhwa, Pakistan. - SAMI UL HAQ (Institut Agama Islam Negeri Palopo, 2019)
This study was conducted to examine the proficiency level of English language reading skill of science students. It focused those components of the curriculum that play a role in its improvement and development. The reading skills and habits of students were also examined through data collected from one hundred and twenty students of Faculty of Biological sciences of the University of Malakand, Khyber Pukhtunkhwa, Pakistan, through a questionnaire. The data were analysed using simple percentages method.The findings of the study revealed that the students had improved reading skill up after taking admission in the university. The study concludes that the inclusion of English language courses as compulsory part of the curriculum had a positive contribution. It also concludes that employing effective teaching strategies and giving more space to the language course was of great help in nurturing necessary skills. The study also concludes that English language input is necessary and played pivotal role in the academic journey of the students in dealing with other subjects in a teaching situation where the medium of instruction is English.